Electrocoagulation technology for high strength arsenic wastewater: Process optimization and mechanistic study. (10th October 2018) - Gilhotra, Vishakha; Das, Laxmi; Sharma, Ambika; Kang, Tejwant S.; Singh, Palwinder; Dhuria, Radhey S.; Bhatti, Manpreet S.
Abstract: In this study, electrocoagulation using stainless steel electrode for removal of arsenic was investigated in an effort to use it for the treatment of water contaminated with high concentration of arsenite (10–100 ppm). A robust and low-cost method for arsenic testing was developed. This method involves reacting arsine gas with silver diethyldithiocarbamate to generate a red coloured compound which was quantified spectrophotometrically at 520 nm. The significant process variables (pH and treatment time) were varied at five levels as per response surface methodology (RSM) approach. The optimized process conditions (pH 5.2 and treatment time = 20 min) for 10 ppm were used to check treatment efficiency at 55–100 ppm of initial arsenic concentration. Other fixed variables were current density 20 A/m 2 and inter electrode distance = 15 mm which resulted in removal efficiency of 99.6% and 86% for 10 ppm and 100 ppm of arsenic respectively. Zeta (ζ) potential, fourier transform infrared spectroscopy and cyclic voltammetry studies indicated a two-step arsenic removal mechanism where As(III) is oxidized to As(V) followed by the adsorption of As(V) onto iron oxide/hydroxide. Mass spectrometric analysis revealed the formation of a complex between iron oxide/hydroxide and arsenite during the electrocoagulation process. Scanning electron microscopy-energy dispersive X-ray images of the settled sludge show amorphous structures on the surface of flocs of iron oxide/hydroxide and confirm the removal of arsenic from the water sample. Waste elimination with electrocoagulation is a sustainable treatment technology with quick start-up, shorter treatment time and minimum sludge generation. Graphical abstract: Image 1 Highlights: Arsenic wastewater (10–100 ppm) was treated with stainless steel electrodes. Response surface methodology was used for process optimization and modelling. Spectrophotometric determination of arsenic at λ max = 520 nm. Mechanism of As(III) oxidation and As(V) adsorption was elucidated. Characterization of electrocoagulation by-products using SEM-EDX and XRD.